Sosialisasi Regulasi Dan Implementasi Denda Pada Spam Pematang Rahim Melalui Pendekatan Komunitas Berbasis Media Sosial - Bambang; Khusnul Yatima; Kurniawan; Hasna Dewi; Ahmad Ihya'ulumuddin (CV. Akira Java Bulu, 2025)
This community service activity aims to increase public understanding and awareness of regulations and the implementation of fines in the Pematang Rahim Village Drinking Water Supply System (SPAM). Outreach was conducted through a community approach utilizing social media as a means of communication and education. Implementation methods included initial observation, educational content creation, and interactive online and offline discussions. The results of the activity showed an increase in public understanding of SPAM regulations from 45% to 87%, knowledge of the fine system from 32% to 80%, and compliance with timely payments from 58% to 90%. Furthermore, community participation in community discussions also increased from 40% to 85%, indicating growing awareness and active community involvement in the management of clean water services.